Application of external waterproofing system with crystalline technology to increase the durability of concrete - Choursoglou Dimitrios; Sideris Kosmas K.; Manita P. (MATEC Web of Conferences, 2025)
Τhe aim of this work is to verify the increase in durability of concrete after the application of an external waterproofing system with crystalline technology. More specifically, two water tanks were cast with two different classes of concrete. These tanks were then filled with water. External waterproofing crystalline system was applied with a surface coating on one of the four sides of each tank. After the completion of eight months from the application of the system, core samples were taken from each tank from the sides where the material had been applied as well as from those that remained intact. These samples after appropriate preparation were subjected to chloride resistance, carbonation and water absorption tests according to European standards. From the results of the conducted tests and the comparison between them, for each tank, safe conclusions about the durability of the concrete were drawn. It was concluded that the application of the external waterproofing system with crystalline technology increased the durability indicators in both concrete tanks. These resulted to the increase of the service life of the concrete sealed with the specific material